Analisis Potensi Ekonomi Sektoral Kabupaten Kolaka Timur - Kartomo Kartomo; Sapriyadi Sapriyadi; Sri Fatmasari Syam (Universitas Batanghari Jambi, 2023)
East Kolaka Regency is one of the regencies in Southeast Sulawesi Province which was only formed in 2013, the development efforts that have been carried out are inseparable from the development problems that are still being faced including problems of economic growth and income inequality. This can be seen from economic growth which tends to decline and the Gini ratio index which has not shown a consistent decline over the past few years. This study aims to determine which economic sectors are categorized as economic sectors that have high, medium, and low potential in East Kolaka Regency. The type of research used is descriptive quantitative. The type of data used is secondary data in the form of GRDP data for East Kolaka Regency during 2014-2021. Data collection techniques were carried out through online searches on the official website of the Central Statistics Agency for East Kolaka Regency and Southeast Sulawesi Province. The data analysis techniques used to determine sectoral economic potential in East Kolaka Regency consist of three, namely: location coefficient analysis (Location Quotient), production growth rate, and the contribution of the economic sector to GRDP formation. The results showed that the economic sectors that have medium potential in East Kolaka district are agriculture, forestry and fisheries, mining and quarrying, construction, and wholesale and retail trade, car and motorcycle repair. While the rest are in the medium potential category.